Inaktivasi Termal Spora Bacillus Subtilis Dalam Jus Nanas - Sakinah Rhajani; Evelyn Evelyn; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Bacillus subtilis is a spore-forming bacterium and has been identified as spoilage in fruit-based medium such as pineapple and tomato. Spores of B. subtilis are heat resistant bacteria. Food preservation by thermal processing is a conventional method and is still used today. The purpose of this study was to determine the effect of temperature (T: 90 °C, 95 °C, 100 °C) and soluble solid 12 °Brix on the thermal inactivation of B. subtilis spores. Then, the kinetics of first order was also investigated in thermal process of B. subtilis in pineapple juice (D-value and the z- value). The D-values obtained at SS 12 ° Brix and temperatures of 90, 95, 100 °C were 13.38; 6.75, and 2.11 minutes. It was shown that higher temperature resulted in the decreasing of the time needed to inactivate the spores. Higher resistance of the spores were observed at higher SS. The results of this study indicate the importance of temperature and soluble solid for heat resistance of B. subtilis spores in pineapple juice. Keywords: Bacillus subtilis, Inactivation, Pineapple juice, Resistance, Spores